Tipificación de la sanción por paro patronal ilegal en el Código Orgánico Integral Penal Ecuatoriano - Sánchez Mera, katherine Michelle (2022)
The present research called Typification of the sanction for illegal employer unemployment in the Organic Integral Criminal Code, is guided by the study of current applicable regulations, international law and other historical precedents of collective labor law, which, in Ecuador, have played an important scenario to give benefits to the party with the greatest need for protection, as are the workers. Without leaving aside the employers, to whom the Constitution of the Republic also refers to a right to demonstrate, called the employer strike, the same tool that was incomplete starting with the publication of the new Organic Integral Criminal Code, which did not contain said sanctioning article, and proceeding to generate greater doubts before the application of the Humanitarian Support Law, which also does not reflect how the issues of collective labor disputes are regulated or at least, does not mention how to deal with such situations. Having clarified both points, it will be demonstrated through the instruments and research techniques carried out to different employers and workers of different companies, in conjunction with the opinion of experts in the management of such situations, the need for the object of study of this thesis project, granting the appropriate conclusions, recommendations and proposal at the end of it, to allow the country to advance in matters of collective labor law, so that they do not harm any of the parties, nor in relation to job stability or the performance of their functions within the companies to which workers in the Ecuadorian productive sector belong.